VEGF as a Marker of Wound Healing: Better High or Better Low? - Kenny Wijaya Sutanto; Endang Sri Lestari; Sigit Adi Prasetyo (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Vascular Endothelial Growth Factor (VEGF) is a key regulator of angiogenesis and tissue regeneration in wound healing. However, the prognostic significance of VEGF expression remains controversial, with both high and low levels variably associated with good or impaired wound healing. This review aimed to clarify the prognostic implications of VEGF expression in wound healing, focusing on whether high or low levels better pred ict favorable outcomes. Methods: A systematic search was conducted in PubMed, EBSCOHost, Embase, and Google Scholar using PRISMA guidelines. Studies involving VEGF measurements in human or animal models of acute and chronic wounds were included. VEGF levels were correlated with healing parameters such as angiogenesis, re-epithelialization, inflammation, and overall wound resolution. Risk of bias was assessed using Cochrane RoB 2.0 and the Newcastle-Ottawa Scale. Result: 15 studies met inclusion criteria. High VEGF levels were oftenly associated with improved outcomes in early wound phases by enhancing angiogenesis. However, sustained high levels in chronic wounds often correlated with unresolved inflammation and fibrosis. In contrast, low VEGF expression indicates impaired angiogenesis. Conclusions: VEGF expression is related to the ongoing phase of wound healing. High levels are beneficial during the acute phase, but if sustained, it may exert negative effects. Clinical interpretation should consider wound type, timing, and VEGF source, rather than relying on absolute expression levels alone.